FRAUD PENTAGON DAN FRAUDULENT FINANCIAL STATEMENT DENGAN BENEISH M-SCORE MODEL PADA INDUSTRI PERBANKAN - Aditya Rizky Fauza; Novita Novita; Michelle Dewi Novandi (Universitas Trilogi, 2026)
Using the Beneish M-Score model, this research examines the impact of pentagon fraud on the detection of indications of financial statement fraud. This study uses logistic regression analysis on a sample of 46 banking companies listed on the Indonesia Stock Exchange from 2021 to 2023. The results show that audit opinions and changes in directors have a significant negative effect on fraudulent financial reports. Financial stability, external pressure, ineffective monitoring, digitalization, and the frequency of CEO changes do not affect fraudulent financial reports. This research contributes to the application of the Beneish M-Score model in identifying indications of fraud in financial reports, as measured by the fraud pentagon elements. Keywords: Beneish M-Score model; Fraudulent financial statement; Pentagon fraud